1) (2x + y)² = 4x² + 4xy + y²
2) (a + 3в)² = a² + 6aв + 9в²
3) (1 - 2x)² = 1 - 4x + 4x²
4) (5 - 4a)² = 25 - 40a + 16a²
5) (6в + 10)² = 36в² + 120в + 100
6) (8y - 5x)² = 64y² - 80xy + 25x²
Пошаговое объяснение:
Формула квадрата суммы: (a + b)² = a² + 2ab + b²
Формула квадрата разности: (a - b)² = a² - 2ab + b²
1) (2x + y)² = (2x)² + 2 * 2x*y + y² = 4x² + 4xy + y²
2) (а + 3в)² = а² + 2 * 3в*а + (3в)² = а² + 6ав + 9в²
3) (1 - 2x)² = 1² - 2 * 1*2x + (2x)² = 1 - 4x + 4x²
4) (5 - 4a)² = 5² - 2 * 5*4a + (4a)² = 25 * 40a + 16a²
5) (6в + 10)² = (6в)² + 2 * 6в*10 + 10² = 36в² + 120в + 100
6) (8y - 5x)² = (8y)² - 2 * 8y*5x + (5x)² = 64y² - 80xy + 25x²